Cytokine production in an ex vivo model of SARS-CoV-2 lung infection - Vorobyeva, Daria A.; Potashnikova, Daria M.; Maryukhnich, Elena V.; Rusakovich, George I.; Tvorogova, Anna V.; Kalinskaya, Anna I.; Pinegina, Natalia V.; Kovyrshina, Anna V.; Dolzhikova, Inna V.; Postnikov, Alexander B.; Rozov, Fedor N.; Sotnikova, Tatiana N.; et al. (Frontiers in Immunology, 2024)
The mechanisms of the SARS-CoV-2-triggered complex alterations in immune cell activation and production of cytokines in lung tissue remain poorly understood, in part because of the limited use of adequate tissue models that simulate the structure and cell composition of the lung in vivo. We developed a novel ex vivo model of SARS-CoV-2 infection of lung explants, that maintains the intact tissue composition and the viral load for up to 7-10 days. Using this model, we studied cytokine production during SARS-CoV-2 infection. We measured a panel of 41 cytokines using xMAP technology, finding an elevation in concentrations of G-CSF, GM-CSF, GRO-α, IFN-γ, IL-6, IL-8, IP-10, MCP-3, MIP-1α, PDGF-AA, and VEGF, and a decrease of IL-1RA concentration in infected tissue in comparison with non-infected explant tissue. These results generally reflect the data obtained in COVID-19 patients. GRO-α, IFN-γ, IL-6, IL-8, MCP-1, MCP-3, and RANTES correlated with the viral load, forming a distinct cluster. In conclusion, our lung ex vivo model faithfully reproduces some aspects of cytokine alterations in COVID-19 patients at an early stage of the disease, thus making the investigation of SARS-CoV-2 infection mechanisms more accessible and providing a potential platform for antiviral drug testing.